Deposit formation in the injector of a diesel engine fueled with higher blended palm biodiesel - Omar, Ghazali; Hamzah, Afiqah; Akop, Mohd Zaid; Zakaria, Mohd Hafidz; Rosli, Nur Natasha Atikah (Malaysian Tribology Society (Mytribos), 2022)
Diesel injection nozzles are precisely machined in the micrometre order to produce a fine fuel spray that is crucial for the engine’s combustion and emission efficiency. This paper studies the deposition in a single-cylinder 4-stroke diesel engine fuel injector nozzle hole using higher blended biodiesel blends. Using B10 and B30, palm biodiesel blends in two separate engine runs, two sets of injectors are collected. The injectors are cross-sectioned to reveal the nozzle hole of the injectors. Scanning electron microscope (SEM), profilometer and electron dispersive X-ray spectroscopy (EDS) analysis of the injector hole surface are presented. The deposit structure is more precipitate type near the inlet and changes to multi-layered type near the outlet. The deposition in the fuel injector hole using a higher biodiesel percentage (B30) produce deposits with a bigger diameter as indicated by the 70% increase in average surface roughness than the deposition in the B10 injector hole.